"Bet you think this song is about you": Whose Narrative Is It in Narrative Research? - Josselson, Ruthellen (Narrative Works, 2011)
This paper examines the dilemmas in narrative research created by the gaps between the authority of experience (the participant’s understanding of his or her life) and the authority of expertise (the researcher’s interpretive analysis of that life). It raises the question of who, at various levels, "owns" the narrative. Using a detailed case example, the paper explores the relationship between authority and authorship as it contrasts the researcher’s intention and the participant’s reactions to what is presented. Ethical dilemmas that ensue are not easily managed, but a suggestion is offered. The dynamics of narcissism that underlie the interpersonal stress of telling another’s life are also considered.